1900 S.C. Acts 449, No. 254, § 1. - (:unkn) unknown (General Publisher, 1900)
That any person who shall, without just cause or excuse, or while under the influence, or feigning to be under the influence of intoxicating liquors, engage in any boisterous conduct, or who shall, without just cause or excuse, discharge any gun, pistol or other firearm while upon or within fifty yards of any public road or highway, except upon his own premises, shall be guilty of a misdemeanor, and, upon conviction thereof, shall pay a fine of not more than one hundred dollars, or beimprisoned for not more than thirty days.
--
Keywords: DISCHARGE